DEMOCRACY AND MANAGING CIVIL-MILITARY RELATIONS: INDONESIA EXPERIENCE - Andhik Beni Saputra (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2018)
The idea of democratic rule requires that democratically elected civilian government should have effective authority over the army. The role of national army is purely for defence. Army’s direct involvement in politics will undermine its capability to cope with external threats. Indonesia is an example where the army was deeply involved in the country’s political affairs. This article shows that Indonesian national army has already possessed political orientation since the beginning of Indonesia’s independence. Military and political functions performed by the Indonesian army during revolutionary war has been influential factor in shaping army’s doctrine and self-perception of his role as not only the guardian of the state but also political force of the country. The weakness of civilian institutions, elite conflicts and national culture especially Javanese tradition has contributted as well to this situation. The role of Indonesian army in politics has gradually decreased since the reform of Indonesia’s political system initiated in 1998.